Between the Conceived and the Lived, the Practiced: the Crossing of Spaces at the Arts and Crafts Fair of Namorados Square in Vitória / ES, Brazil - Domingues, Fabiana Florio; Fantinel, Letícia Dias; Figueiredo, Marina Dantas de (Organizações & Sociedade, 2019)
This article aims to understand how the organizational space of a fair (the Arts and Crafts Fair of the Namorados Square, in Vitória, Espírito Santo) constitutes itself in the intersection of uses that different subjects adopt in the urban space. For this, we used an ethnographic method, with the data being produced from systematic and participative observation between May and October 2015. We examined the data based on categories articulated from the theoretical propositions of the authors Henri Lefebvre and Michel De Certeau. Results show that the organization of the fair is determined by provisional practices, whose existence is permeated by manifestations of power, resistance and conflict which emerge from the daily life of the subjects. By revealing forces that act by forming ephemeral harmonies, we show the intersections of space conceived and lived. The fair, as an organizational form, emerges from the juxtaposition of uses and appropriations of its spaces, in a dynamic that privileges space concepts elaborated by certain subjects and then sometimes by others.